Are Indian Startups Technology Driven ? Investigating Potentiality of Indian Startups - Rajpara, Yashasvi (AMC Indian Journal of Entrepreneurship, 2020)
The aspect which hinders technology driven entrepreneurship is weak intellectual property rights (IPR) protection. India was ranked second from bottom among 30 countries examined for IPR protection as per the 2015 GIPC Index of the US Chamber of Commerce. Weak IPR laws and enforcement continue to limit the ability of businesses to invest in R&D. Inadequate IPR protection could also discourage multinationals from setting up operations in India or in bringing their technology into the country. To foster innovation in terms of technology, both home-grown and imported, and to attract international partners who bring technology and global best practices, a country must have in place robust institutional and legal mechanisms to protect IPR. This needs to be prioritized by the Indian government as part of its national growth agenda to promote technology driven entrepreneurship. To boost the startup enterprises in India along with market driven entrepreneurship, technology driven entrepreneurship has to be developed. Here in this paper an attempt was made to sincerely study startups from a technology point of view and not from the market point of view.